Branding and Social Media Strategies for Mama-Mama Papua Culinary Competitiveness - Lisa Gresti Sella Damanik; Palti Maretto Caesar Manalu; Rizka Cintya Edwar (Media Ekonomi dan Manajemen, 2026)
This study examines the contribution of local identity-based branding and social media optimization to enhancing the competitiveness of Mama-Mama Papua culinary enterprises in Jayapura City. The research employed a qualitative case study approach involving traditional culinary businesses managed by Mama-Mama Papua. Data were collected through semi-structured interviews, direct observations, and documentation, and analyzed using thematic analysis to identify patterns related to branding practices, social media utilization, and business competitiveness. The findings reveal that product authenticity, the use of local ingredients, and Papuan cultural values serve as the main sources of brand differentiation and strengthen the uniqueness of culinary products. However, branding implementation remains limited, particularly in product packaging and visual identity, while the utilization of social media for business promotion varies depending on the entrepreneurs’ digital literacy. Despite these limitations, social media has expanded market reach and improved customer engagement. In conclusion, strengthening local identity-based branding supported by effective social media utilization plays an important role in improving the competitiveness and sustainability of Mama-Mama Papua culinary enterprises.